2006
DOI: 10.1177/0146167205282737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mortality Salience on Evaluation of Ingroup and Outgroup Sources: The Impact of Pro- Versus Counterattitudinal Positions

Abstract: Past Terror Management Theory (TMT) research has demonstrated that mortality salience leads to favoritism toward ingroup members and derogation of outgroup members and to polarized attitudes toward the source of pro and counterattitudinal statements. In such research, the individual's group membership and the individual's worldview position were examined separately. Thus, when the individual's group membership was manipulated, one could normally assume that an outgroup member is counterattitudinal and an ingro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
2
29
4
1
Order By: Relevance
“…Besides going beyond the research by Arndt et al () and Dechesne, Greenberg, et al (), the current findings also showed the opposite pattern of findings compared with other prior research that revealed favoritism toward the in‐group critic over the out‐group critic under mortality salience (See & Petty, ). As suggested earlier, in that research, participants first knew that the critic was an in‐group member before learning about the critic's comments (See & Petty, ).…”
Section: Discussioncontrasting
confidence: 82%
“…Besides going beyond the research by Arndt et al () and Dechesne, Greenberg, et al (), the current findings also showed the opposite pattern of findings compared with other prior research that revealed favoritism toward the in‐group critic over the out‐group critic under mortality salience (See & Petty, ). As suggested earlier, in that research, participants first knew that the critic was an in‐group member before learning about the critic's comments (See & Petty, ).…”
Section: Discussioncontrasting
confidence: 82%
“…One way to think about TMT is as a lens through which to understand the functional significance of different domains of human social behavior. In this light, the theory has been applied to understanding how our existential distress relates to a number of traditional domains of social psychological inquiry, such as aggression (e.g., H. McGregor et al., 1998), self‐awareness processes (e.g., Arndt et al., 1998), social influence and persuasion (See & Petty, 2006), conformity and distinctiveness (e.g., Simon et al., 1997a), attitude behavior consistency (e.g., Friedman & Arndt, 2005), and altruism (e.g., Jonas et al., 2002). In this next section, we offer a few examples of how researchers have used this lens to understand the cognitive architecture underlying the processing of thoughts about death, the basic ways in which our identity construction interfaces with managing existential concerns, and how these ideas can be applied to pressing social issues.…”
Section: Some Recent Trajectories Of Terror Management Researchmentioning
confidence: 99%
“…), derogation of counter-attitudinal outgroup members (e.g., See and Petty 2006), and endorsement of materialistic goals (e.g., Kasser and Sheldon 2000). Presumably, cultural status confers a sense of value in a rulebound and meaningful social universe, both of which provide relief from the simultaneous certainty of death and the uncertainty of when, how, or why one's death will occur.…”
mentioning
confidence: 99%